A method for preparing a magnesium silicate hydrate-based water-responsive gel material

CN118771763BActive Publication Date: 2026-10-20UNIV OF SCI & TECH LIAONING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411141688.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2026-10-20
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

[0005]本发明主要目的是为了解决实际工程上常需要便于拆除的一次性构件的问题,提供一种易拆除、高强度、体积随变的材料,发明的一种水化硅酸镁基水响应凝胶材料的制备方法

Benefits of technology

[0019]1、本发明以菱镁尾矿制备的高活性氧化镁粉为原料,低碳环保,降低了成本,且氧化镁粉活性高,有利于产品性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771763B_ABST
    Figure CN118771763B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a magnesium silicate hydrate-based water-responsive gel material, and the water-responsive phenomenon of the magnesium silicate hydrate is excited by adjusting the environmental humidity; the overall preparation process is simple and environmentally friendly, the prepared magnesium silicate hydrate-based water-responsive gel material is stable in structure, high in strength, good in fluidity and high in practical value, the water-responsive speed can be fine-tuned by adjusting the environmental humidity; the preparation method comprises the following steps: dry mixing and stirring, solution preparation, slurry preparation, molding, water bath curing, water-responsive curing and the like, so that the magnesium silicate hydrate-based water-responsive gel material at normal temperature is obtained, and the shrinkage rate of the obtained product can be adjusted by changing the curing temperature and humidity; the magnesium silicate hydrate-based water-responsive gel material of the application makes certain necessary limitation to the application of the magnesium silicate hydrate cement in the building material field, expands the practical value of the magnesium silicate hydrate cement in the field outside the traditional building material field, and has great influence on some application fields of high-precision and high-strength materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, specifically to a method for preparing a hydrated magnesium silicate-based water-responsive gel material. Background Technology

[0002] Traditional silicate cement production releases significant amounts of carbon dioxide into the atmosphere. Hydrated magnesium silicate cement, however, is a more environmentally friendly green building material. Its smaller pore size and porosity give it excellent water resistance, and its low pH value makes it suitable for marine engineering applications. Its lower carbon emissions also align with national policies. Compared to traditional silicate cement, hydrated magnesium silicate cement has better surface gloss and lower porosity, and is widely considered a valuable cementitious material. However, it also suffers from low early strength and large drying shrinkage, which severely restricts its promotion and application. In-depth research has revealed a close relationship between the drying shrinkage of hydrated magnesium silicate and environmental humidity. During curing at different humidity levels, hydrated magnesium silicate cement exhibits a certain water response phenomenon. This phenomenon reveals the reason for the limited use of hydrated magnesium silicate cement in traditional cement applications, and also expands its application prospects in other fields.

[0003] To address the problems of low strength and high shrinkage in hydrated magnesium silicate, extensive research has been conducted both domestically and internationally. Chinese patent CN113620687B discloses a method for preparing hydrated magnesium silicate-based cementitious materials containing sulfur-oxygenated magnesium-based waste. By adding sulfur-oxygenated magnesium-based waste, the density and compressive strength of hydrated magnesium silicate cement are improved, its fluidity is enhanced, and shrinkage deformation is reduced. This method improves the performance of hydrated magnesium silicate cement while increasing the recycling rate of sulfur-oxygenated magnesium-based waste; however, its shrinkage rate is relatively high. Chinese patent CN109896808B discloses a method for preparing [material] based on magnesite tailings. Magnesium silicate system cementitious materials and their preparation methods: Using lightly calcined magnesium oxide powder obtained from low-grade magnesite tailings and active silica formed from waste products of ferrosilicon smelting as raw materials, magnesium silicate system cementitious materials are prepared, which greatly reduces the cost of raw materials for the entire process. However, it does not perform water-responsive curing on the cementitious materials, resulting in a high drying shrinkage rate. Chinese patent CN109896808B discloses a method for preparing magnesium silicate using quartz sand as a siliceous raw material, which involves steam curing and high-temperature and high-pressure reaction. Although it obtains hydrated magnesium silicate gel with high strength, it wastes a lot of energy.

[0004] By adjusting the curing humidity, the density of hydrated magnesium silicate cement can be increased, thereby improving its basic compressive strength. This also allows for controllable volume changes, directly solving the problem of excessive drying shrinkage and making it suitable for high-precision applications. While its unique water-responsive phenomenon limits its application in traditional building materials, it also opens up broader and more promising applications. Summary of the Invention

[0005] The main purpose of this invention is to solve the problem of easily removable disposable components often needed in practical engineering, and to provide a material that is easy to remove, has high strength, and varies in volume. The invention also includes a method for preparing a hydrated magnesium silicate-based hydroresponsive gel material.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: a method for preparing a hydrated magnesium silicate-based hydroresponsive gel material, characterized in that the production process of the hydrated magnesium silicate-based hydroresponsive gel material specifically includes the following steps:

[0007] Step 1: Dry mixing. Select a certain amount of the high-activity magnesium oxide powder and active silica and vibrate them through a sieve. Mix the two sieved powders thoroughly to obtain a dry mixture.

[0008] Step 2: Prepare the solution by adding a fixed amount of water-reducing agent and water to a container and mixing thoroughly to obtain the solution;

[0009] Step 3: Slurry preparation. Add the dry mixture to the solution and stir continuously to obtain a slurry of hydrated magnesium silicate-based gel material.

[0010] Step 4: Molding. The hydrated magnesium silicate-based gel material slurry is poured into a mold and then moved to a vibration table for 30-60 seconds. The mold is then moved to a curing chamber with a temperature of 20±2℃ and a relative humidity of ≥90% for 24±2 hours before demolding.

[0011] Step 5: Water bath curing. After demolding, the sample is cured in a water bath at a temperature of 20±2℃ for 28 days to obtain hydrated magnesium silicate-based gel material.

[0012] Step 6: Water-responsive curing. The hydrated magnesium silicate-based gel material is transferred to an environment with a temperature of 20±2℃ and a relative humidity of <70% for continuous curing, thus obtaining the hydrated magnesium silicate-based water-responsive gel material.

[0013] Furthermore, after 28 days of water bath curing, water response curing is required for at least 7 days.

[0014] Further, the mixture contains 35-45 parts of highly active magnesium oxide powder, 55-65 parts of silica fume, 45-55 parts of water, and 1-3 parts of water-reducing agent.

[0015] Furthermore, add 3-4 parts of graphite powder during the dry mixing process.

[0016] Furthermore, the high-activity magnesium oxide powder, measured by hydration, has an activity of not less than 60%, a specific surface area of ​​24.8 m² / g, and a particle size of 200 mesh; the silica fume contains not less than 95% silica, has a specific surface area of ​​21.9 m² / g, and a particle size of 200 mesh.

[0017] Furthermore, the water-reducing agent is one of sodium hexametaphosphate, trisodium phosphate, or sodium metaphosphate.

[0018] The features and beneficial effects of this invention are as follows:

[0019] 1. This invention uses highly active magnesium oxide powder prepared from magnesite tailings as raw material, which is low-carbon and environmentally friendly, reduces costs, and the magnesium oxide powder has high activity, which is beneficial to product performance.

[0020] 2. This invention uses hydrated magnesium silicate-based gel material as the main raw material. The product is lightweight, high-strength, low-carbon, environmentally friendly, and has good fire and water resistance. Its performance can be improved by adding other materials without affecting the water response phenomenon.

[0021] 3. The hydrated magnesium silicate-based water-responsive gel material of the present invention has high water sensitivity, and the size of the product can be finely adjusted by adjusting the ambient humidity (even the shrinkage rate can be adjusted to 0%), which solves the problem of excessive drying shrinkage of hydrated magnesium silicate gel.

[0022] 4. The hydrated magnesium silicate-based water-responsive gel material of the present invention can maintain structural stability and mechanical strength for a long time. After water-responsive curing, the material responds quickly to water, and the fragment size after breakage is small, and the fragment size decreases with the extension of water-responsive curing time.

[0023] 5. The manufacturing method of the present invention does not require high-end equipment. Only an ordinary mixer is needed to complete all operations. Moreover, the entire production process is simple to operate, environmentally friendly and controllable, and the raw materials are non-toxic and non-corrosive. Attached Figure Description

[0024] Figure 1 The graph shows the test results of the volume change rate of the samples in Examples 1 and 2;

[0025] Figure 2 The graph shows the test results of the volume change rate of samples from Comparative Example 1 and Comparative Example 2.

[0026] Figure 3 This is a graph showing the fragment size test results after water response in Example 1. Detailed Implementation

[0027] Evaluation scheme for hydrated magnesium silicate-based hydroresponsive gel materials:

[0028] The hydrated magnesium silicate-based hydroresponsive gel material was cast into compressive strength specimens of 40mm×40mm×40mm and shrinkage specimens of 40mm×40mm×160mm.

[0029] Evaluation process

[0030] Step 1, Slurry flowability test:

[0031] The flowability of the sample was tested according to the "Flowability of Cement Paste" section of the "Test Method for Homogeneity of Concrete Admixtures" (GB / T8077-2012). A truncated cone mold was placed in the center of a glass plate. The well-mixed hydrated magnesium silicate-based hydroresponsive gel material was quickly poured into the truncated cone mold and leveled with a scraper. The truncated cone mold was lifted vertically while a stopwatch was started. The cement paste was allowed to flow on the glass plate for 30 seconds. Afterward, the maximum diameter of the flowing portion in two mutually perpendicular directions was measured with a ruler, and the average of the two measurements was taken as the flowability of the cement paste.

[0032] Step 2: Compressive strength test

[0033] Using a YDE-300D universal testing press, the compressive strength of cubic specimens aged 28d, 35d, and 56d was tested at a loading rate of 2.4kN / s. Six specimens were taken from each group, and the average value of the compressive strength results was taken.

[0034] Step 3, Shrinkage test:

[0035] The shrinkage rate of the test specimens was tested according to the JC / T603-2004 standard for the building materials industry. An ISOBY-160 length comparator was used to measure the changes in the specimen length (l0) after demolding at 3d, 7d, 11d, 14d, 17d, 21d, 24d, 28d, 31d, 35d, 39d, 42d, 45d, 49d, 52d, and 56d. Three specimens were used in each group, and the results were averaged. The shrinkage rate of the specimens was calculated using the formula:

[0036]

[0037] Where: ε st Shrinkage rate (%); l0: Initial length of the sample (mm); l1: Length of the sample at different ages (mm)

[0038] The present invention will be described in detail below with reference to the embodiments, but the scope of the present invention is not limited to the following embodiments.

[0039] Within the scope of this invention, the sample subjected to a water-responsive curing environment of 20±2℃ and 65±3% relative humidity is Example 1; the sample subjected to a water-responsive curing environment of 20±2℃ and 65±3% relative humidity and incorporating 4% 800-mesh graphite is Example 2, wherein graphite is used as filler aggregate 2. Additionally, a sample subjected to water bath curing without water-responsive curing is Comparative Example 1; a sample subjected to neither water bath curing nor water-responsive curing, but consistently cured in an environment of 20±2℃ and >90% relative humidity, is Comparative Example 2.

[0040] Example 1:

[0041] The raw material composition is: 600g of highly active magnesium oxide powder, 900g of silica fume, 750g of deionized water, and 30g of sodium hexametaphosphate;

[0042] The high-activity magnesium oxide powder, measured by hydration, had an activity of not less than 60% and a specific surface area (BET method) of 24.8 m². 2 / g, particle size 200 mesh, silica content in silica fume not less than 95%, specific surface area (BET method) 21.9m² 2 / g, particle size 200 mesh.

[0043] The preparation process is as follows:

[0044] Vibrate and sieve all the high-activity magnesium oxide powder and silica fume through a 200-mesh sieve. Weigh 600g of the high-activity magnesium oxide powder and 900g of the silica fume that passed through the sieve, and pour them into a cement mixing pot. Start slow stirring until the high-activity magnesium oxide powder and silica fume in the pot are fully mixed. Remove all the dry mixture and set it aside. Weigh 30g of reagent-grade sodium hexametaphosphate and pour it into the cement mixing pot. Then weigh 750g of water and pour it into the cement mixing pot. Start slow stirring for 30 minutes until the sodium hexametaphosphate is fully dissolved to obtain a sodium hexametaphosphate solution. Start the mixing pot and stir slowly. While stirring slowly, pour the dry mixture into the mixing pot along the wall of the pot at a decreasing speed, first fast and then slow, controlling the pouring time to be within 2-3 minutes. After it is completely added, use a scraper to scrape the dry mixture off the stirring rod, the bottom of the mixing pot, the pot wall, and the plastic sheet. Stir slowly again for 10 seconds, then increase the speed and stir for 2 minutes. At this time, the slurry gradually forms, and the hydrated magnesium silicate-based gel material slurry is obtained. A small amount of hydrated magnesium silicate-based gel material slurry was taken for a flowability test. After vibrating on a shaking table for 60 seconds, excess slurry was scraped off the mold with a scraper. The mold was then placed in a constant temperature and humidity curing chamber at 20±2℃ and relative humidity >90% for 24±2 hours. Small amounts of hydrated magnesium silicate-based gel material slurry at 3d, 7d, 11d, 14d, 17d, 21d, 24d, 28d, 31d, 35d, 39d, 42d, 45d, 49d, 52d, and 56d were then tested. The compressive strength and shrinkage rate were tested by pouring the sample into a 40mm×40mm×40mm compression sample mold and a 40mm×40mm×160mm shrinkage sample mold. After demolding, the sample was cured in a constant temperature curing chamber at 20±2℃ for 28 days to obtain hydrated magnesium silicate-based gel material. The sample was then transferred to a constant temperature and humidity curing chamber at 20±2℃ and 65±3% for more than 7 days to obtain hydrated magnesium silicate-based water-responsive gel material.

[0045] Step 1, Slurry flowability test:

[0046] Wipe the glass plate and the truncated cone mold with a damp cloth to ensure they are moist but without water stains. Place the truncated cone mold in the center of the glass plate. Quickly pour the well-stirred hydrated magnesium silicate-based gel slurry into the truncated cone mold and smooth it with a scraper. While lifting the truncated cone mold vertically, start a stopwatch and allow the cement slurry to flow on the glass plate for 30 seconds. Then, use a ruler to measure the maximum diameter of the flowing part in two mutually perpendicular directions. Take the average of the two measurements as the flowability of the cement slurry. The results are shown in Table 1.

[0047] Step 2: Compressive strength test

[0048] The compressive strength of 40mm×40mm×40mm cubic specimens aged 28d, 35d, and 56d was tested using a YDE-300D universal testing press at a loading rate of 2.4kN / s. Five specimens were taken from each group, and the average value was used as the compressive strength value to evaluate the compressive performance. The results are shown in Table 1.

[0049] Step 3, Shrinkage test:

[0050] The shrinkage rate of the test specimens was tested according to the JC / T603-2004 standard for the building materials industry. An ISOBY-160 length comparator was used to measure the length (l0) of the specimens after demolding and the changes in length at 3d, 7d, 11d, 14d, 17d, 21d, 24d, 28d, 31d, 35d, 39d, 42d, 45d, 49d, 52d, and 56d under different treatment conditions. The values ​​were calculated according to the shrinkage rate formula (1). The average of three specimens in each group was taken. The results are as follows: Figure 1 and Figure 2 .

[0051] Example 2:

[0052] The raw material composition is as follows: 600g of highly active magnesium oxide powder, 900g of silica fume, 750g of deionized water, 30g of sodium hexametaphosphate, and 60g of graphite.

[0053] The preparation method of Example 2 is similar to that of Example 1, except that 60g of graphite is added to the raw material composition.

[0054] The sample evaluation process in Example 2 is the same as in Example 1.

[0055] Comparative Example 1:

[0056] The raw material composition of Comparative Example 1 is the same as that of Example 1.

[0057] The preparation method of Comparative Example 1 is similar to that of Example 1, except that after demolding, the sample is cured in a water bath at a temperature of 20±2℃ for 56 days, instead of being cured in a constant temperature and humidity chamber with a relative humidity of 65±3%.

[0058] The evaluation process for the sample in Comparative Example 1 is the same as that in Example 1.

[0059] Comparative Example 2:

[0060] The raw material composition of Comparative Example 2 is the same as that of Example 1.

[0061] The preparation method of Comparative Example 2 is similar to that of Example 1, except that after demolding, the sample is continuously cured in a constant temperature and humidity curing chamber at a temperature of 20±2℃ and a relative humidity of >90% for 56 days, instead of water bath curing in a constant temperature curing chamber at 20±2℃ and continuous curing in a constant temperature and humidity curing chamber at 20±2℃ and a relative humidity of 65±3%.

[0062] The evaluation process for the sample in Comparative Example 2 is the same as that in Example 1.

[0063] Table 1. Performance test results of samples from Example 1, Example 2, Comparative Example 1, and Comparative Example 2.

[0064]

[0065] As shown in Table 1, the hydrated magnesium silicate-based hydroresponsive gel material of the present invention has a 28-day compressive strength of 29.6 MPa, a 56-day compressive strength of 39.7 MPa, and a flowability of 216 mm. The strength can also be improved by incorporating other materials (4% graphite) (the 28-day compressive strength can reach 31.0 MPa, and the 56-day compressive strength can reach 41.5 MPa).

[0066] from Figure 1 and Figure 2 Data shows that the hydrated magnesium silicate-based water-responsive gel material of the present invention can finely adjust the product volume by changing the curing humidity, making the product volume change controllable, solving the problem of excessive drying shrinkage of hydrated magnesium silicate cement, and facilitating practical application.

[0067] Take the complete 35-day sample from Example 1 and the 56-day sample, place them in water to test the water response. After 24 hours of water response, take all fragments and place them in a vibrating screen for 2 minutes. Measure the fragment size. The results are as follows: Figure 2 .

[0068] from Figure 3 Data shows that the size of the fragments in the hydrated magnesium silicate-based water-responsive gel material of the present invention decreases with the extension of water-responsive curing time. The mass percentage of fragments smaller than 2.36 mm after water response of the 56-day sample is greater than 75%.

[0069] Regarding the water response explanation, in low-humidity environments, the magnesium silicate gel phase in hydrated magnesium silicate cement (MSHC) easily loses some gel water, causing a decrease in mass and volume. When MSHC is placed under 70% humidity for a period of time, it exhibits a completely different water response phenomenon than previous cements: when MSHC is placed in water again, it undergoes a violent water absorption and expansion phenomenon, leading to complete cement breakage. Simultaneously, the volume shrinkage of MSHC can be controlled by adjusting the ambient humidity, thus causing varying degrees of expansion upon re-exposure to water. This method of controlling MSHC volume using humidity allows for arbitrary switching between water damage and water repair, providing a simple, efficient, safe, and environmentally friendly means for its use and removal in one-off projects.

[0070] The hydrated magnesium silicate-based water-responsive gel material of this invention is prepared by controlling the humidity of the curing environment after 28 days of curing, with hydrated magnesium silicate gel as the main system. While ensuring high strength, the drying shrinkage rate of hydrated magnesium silicate is controllable. Furthermore, the strength can be further improved by incorporating other materials, greatly enhancing the product's practicality. The product exhibits excellent flowability, stable structure, simple and efficient process, environmental friendliness, and low cost. Most importantly, it has a rapid water response, small fragment size after water response, and the fragment size can be further reduced by extending the water-responsive curing time, showing great application potential. This is of great significance for improving the practicality of hydrated magnesium silicate cement, increasing its added value, and promoting its future development.

[0071] Unless otherwise specified, the raw materials and experimental equipment used in this invention are commonly used in the field; the experimental methods used in this invention are conventional experimental methods in the field.

[0072] The above embodiments are only some embodiments of the present invention and do not limit the present invention in any way. Any simple modifications, changes and equivalent transformations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a hydrated magnesium silicate-based hydroresponsive gel material, characterized in that, The production process of hydrated magnesium silicate-based hydroresponsive gel materials specifically includes the following steps: Step 1: Dry mixing. Select a certain amount of high-activity magnesium oxide powder and active silica and vibrate them through a sieve. Mix the two sieved powders thoroughly to obtain a dry mixture. Step 2: Prepare the solution by adding a fixed amount of water-reducing agent and water to a container and mixing thoroughly to obtain the solution; Step 3: Slurry preparation. Add the dry mixture to the solution and stir continuously to obtain a slurry of hydrated magnesium silicate-based gel material. Step 4: Molding. The hydrated magnesium silicate-based gel material slurry is poured into a mold and then moved to a vibration table for 30-60 seconds. The mold is then moved to a curing chamber with a temperature of 20±2℃ and a relative humidity of ≥90% for 24±2 hours before demolding. Step 5: Water bath curing. After demolding, the sample is cured in a water bath at a temperature of 20±2℃ for 28 days to obtain hydrated magnesium silicate-based gel material. Step 6: Water-responsive curing. The hydrated magnesium silicate-based gel material is transferred to an environment with a temperature of 20±2℃ and a relative humidity of <70% for continuous curing to obtain the hydrated magnesium silicate-based water-responsive gel material. As the water-responsive curing time increases, the size of the fragments after water response tends to decrease. The water-responsive curing after 28 days of water bath curing should be at least 7 days.

2. The method for preparing a hydrated magnesium silicate-based hydroresponsive gel material according to claim 1, characterized in that, The high-activity magnesium oxide powder consists of 35-45 parts, silica fume 55-65 parts, water 45-55 parts, and water-reducing agent 1-3 parts, by weight.

3. The method for preparing a hydrated magnesium silicate-based hydroresponsive gel material according to claim 2, characterized in that, Add 3-4 parts of graphite powder (by weight) during the dry mixing process.

4. The method for preparing a hydrated magnesium silicate-based hydroresponsive gel material according to claim 2, characterized in that, The high-activity magnesium oxide powder, measured by hydration, showed an activity of not less than 60% and a specific surface area of ​​24.8 m². 2 / g, particle size 200 mesh; silica fume with silica content not less than 95% and specific surface area of ​​21.9m². 2 / g, particle size 200 mesh.

5. The method for preparing a hydrated magnesium silicate-based hydroresponsive gel material according to claim 1, characterized in that, The water-reducing agent is one of sodium hexametaphosphate, trisodium phosphate, or sodium metaphosphate.

Citation Information

Patent Citations

  • A magnesium silicate cementitious material prepared from magnesite tailings and its application

    CN109896808B

  • Hydrated magnesium silicate-based cementitious materials containing sulfur-containing magnesium oxide-based waste and their preparation methods

    CN113620687B